Machine learning, optimization, and big data : first International Workshop, MOD 2015, Taormina, Sicily, Italy, July 21-23, 2015, Revised selected papers /: first International Workshop, MOD 2015, Taormina, Sicily, Italy, July 21-23, 2015, Revised selected papers. (2015) - Unknown
No abstract available